Digital Supply Chain Model for Emergency Management in Thai Universities - Artaphon Chansamut (ExcelingTech, 2023)
The purpose of paper is to study and to evaluate digital supply chain model for emergency management in Thai universities. The research sample totalling ten experts consisted of ten experts consisted of five experts on supply chain , five experts on digital technology. The employed research instrument is a questionnaire. Statistics employed for data analysis are mean and standard deviation.. The research findings digital supply chain model for emergency management in Thai Satisfaction comprises six elements namely main components suppliers, University, Good service and security, Customers and satisfaction. The paper found that digital supply chain model for emergency management in Thai has suitability in a good level that mean the model may be applies in support the tasks.